Carbon governance: A case study of warehouse in Malaysia - Azian, Ibrahim; Fernando, Yudi (Inderscience Enterprises Ltd., 2023)
The detrimental effects of climate change on the economy and the environment have been established through studies, representing how this issue has become a complex global challenge. Previous research has advocated swift action to protect all life from potential threats. A previous study has also endorsed various sustainability initiatives to address the worsening climate change induced by economic operations. As a result, businesses must begin taking action and delegating workers to reduce the amount of carbon that companies emit. The absence of previous research investigating carbon governance and low-carbon warehousing in Malaysian manufacturing industries’ served as the impetus for this investigation. A case study approach was used for this research via semi-structured, in-person interviews with three companies. The results showed that all the companies were concerned with the low carbon warehouse governance. A few organisational theories were identified to be the best fit in supporting the low carbon warehouse governance.